Innowacyjne instrumenty finansowe jako czynnik sprzyjający poprawie spójności ekonomicznej w regionach - Panenka, Alicja (Innovative Financial Instruments as a Factor Facilitating Improvement of Economical Cohesion in Regions, 2006)
Innovations are becoming the key to competitiveness on the international, national and regional level in the conditions of economy based in increasing level on knowledge. This statement was confirmed in the Lisbon Strategy and also in the New Lisbon Strategy that was formed by the European Commission in the 2004, where the main attention was drawn to two objectives: basing the economic growth on knowledge and innovations and increasing employment by creating better jobs. It seems that for less developed regions basing their economies on producing technologically advanced services and products can contribute to the reduction of their economic delay for other regions of EU. In this light the role that is played by innovative financial instruments seems to be important. By using it, the availability of capital for companies introducing or creating new technological solutions is increasing. Poland in the biggest venture capital/private equity market in the Eastern and Central Europe, but the capital gap still exists in the capital market. In spite of couple of years of presence of PE/VC in our market, it's still easier to obtain billions of zlotys for expansion of the company instead of smaller amounts for financing new enterprises. Nevertheless, for the development of venture capital sector the positive influence should have legal and institutional changes that were made in Poland in 2004-2005.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 237-248